2006
DOI: 10.1128/jb.188.9.3371-3381.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chromate Stress on Escherichia coli K-12

Abstract: The nature of the stress experienced by Escherichia coli K-12 exposed to chromate, and mechanisms that may enable cells to withstand this stress, were examined. Cells that had been preadapted by overnight growth in the presence of chromate were less stressed than nonadapted controls. Within 3 h of chromate exposure, the latter ceased growth and exhibited extreme filamentous morphology; by 5 h there was partial recovery with restoration of relatively normal cell morphology. In contrast, preadapted cells were le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
149
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(162 citation statements)
references
References 45 publications
(38 reference statements)
12
149
0
1
Order By: Relevance
“…These results suggested that YqhD may play an antioxidant role by protecting E. coli from the oxidative damage caused specifically by ROS. This YqhD function would be of particular importance when cells encounter compounds that generate superoxide (tellurite) or hydroxyl radicals (chromate) (4, 5) since these toxics also affect cytoplasmic GSH levels (9,29,30). In this context, the hypersensitive phenotype to K 2 TeO 3 and K 2 Cr 2 O 7 observed in E. coli ⌬yqhD could be explained by a dual effect caused by ROS, namely the known direct damage on proteins, DNA, and membrane lipids and, indirectly, the inherent toxicity of peroxides and reactive aldehydes generated by membrane lipid peroxidation, which could not be scavenged in the absence of GSH.…”
Section: Figure 3 Oxidized Proteins In E Coli a Sds-page Showing mentioning
confidence: 99%
“…These results suggested that YqhD may play an antioxidant role by protecting E. coli from the oxidative damage caused specifically by ROS. This YqhD function would be of particular importance when cells encounter compounds that generate superoxide (tellurite) or hydroxyl radicals (chromate) (4, 5) since these toxics also affect cytoplasmic GSH levels (9,29,30). In this context, the hypersensitive phenotype to K 2 TeO 3 and K 2 Cr 2 O 7 observed in E. coli ⌬yqhD could be explained by a dual effect caused by ROS, namely the known direct damage on proteins, DNA, and membrane lipids and, indirectly, the inherent toxicity of peroxides and reactive aldehydes generated by membrane lipid peroxidation, which could not be scavenged in the absence of GSH.…”
Section: Figure 3 Oxidized Proteins In E Coli a Sds-page Showing mentioning
confidence: 99%
“…Chromium occurs mainly in two forms in the environment i.e., trivalent and hexavalent (as chromate and dichromate) and is actively transported to cells (Ortegel et al, 2002). Among the different forms of chromium, the hexavalent chromium is the more toxic and carcinogenic due to its high solubility in water, rapid permeability through biological membranes and subsequent interaction with intracellular proteins and nucleic acids (Kamaludeen et al, 2003;Ackerley et al, 2006). Reduction of Cr (VI) leads to the formation of stables, less soluble and less toxic Cr (III).…”
Section: Introductionmentioning
confidence: 99%
“…One of many possible ways to increase the effectiveness of chromium bioremediation by using bacteria is to alter the expression of these genes to minimize oxidative stress during chromate reduction. This approach has been proposed by several other researchers [12,48]. Previously, we have postulated that the B2-DHA is resistant to chromium and it can decrease chromium content significantly in the contaminated source by accumulating it in the cells [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, chromium has multiple effects on bacteria including competitive inhibition of sulphate transport, DNA mutagenesis and protein damage [8]. Microorganisms have developed various mechanisms to survive chromium toxicity: (i) transmembrane efflux of chromate (ii) the ChrR transport system (iii) the reduction of chromate (iv) protection against oxidative stress and (v) DNA repair systems [3,[9][10][11][12][13][14][15]. In addition, chromate resistance is attributed to the functions of a series of chromosomal or plasmid encoded genes, including the chromium resistance (chr) operon comprising of either chrBAC or chrBACF in bacteria [9,16,17].…”
Section: Introductionmentioning
confidence: 99%